2013
DOI: 10.1038/cddis.2013.170
|View full text |Cite
|
Sign up to set email alerts
|

Sigma-1 receptor agonist PRE084 is protective against mutant huntingtin-induced cell degeneration: involvement of calpastatin and the NF-κB pathway

Abstract: Alterations in mitochondria and increased oxidative stress are associated with the disease progression in Huntington's disease (HD). Endoplasmic reticulum (ER) stress and oxidative damage are linked through the close communication between the ER and mitochondria. Sigma-1 receptor (Sig-1R) is a chaperone protein in the ER that is involved in ER stress regulation, but little is known about its role in HD or the mechanisms for cell protection. Here we show that the Sig-1R agonist, PRE084 increases cell survival a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
99
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 114 publications
(110 citation statements)
references
References 45 publications
4
99
1
1
Order By: Relevance
“…A recent study indicated that overexpression of Sig-1R or addition of Sig-1R agonist increased endogenous calpain inhibitor calpastatin expression in the neuronal PC6.3 cell line (58). However, we found no significant differences in calpain or calpastatin protein levels in Sig-1R KO neurons or when overexpressing Sig-1R in the neuro-2a cells (Fig.…”
Section: Sig-1r Controls P35 Degradation Mainly Through the Proteasomalcontrasting
confidence: 48%
“…A recent study indicated that overexpression of Sig-1R or addition of Sig-1R agonist increased endogenous calpain inhibitor calpastatin expression in the neuronal PC6.3 cell line (58). However, we found no significant differences in calpain or calpastatin protein levels in Sig-1R KO neurons or when overexpressing Sig-1R in the neuro-2a cells (Fig.…”
Section: Sig-1r Controls P35 Degradation Mainly Through the Proteasomalcontrasting
confidence: 48%
“…In relation to HD, the S1R agonist, PRE084, was shown to enhance cellular antioxidant defences and to protect against mHTT-induced toxicity in a rat neuronal cell line (18). Using R6/2 HD mice, pridopidine treatment was shown to improve motor function and survival, effects that were associated with increased striatal BDNF and DARPP-32 levels (19).…”
Section: Discussionmentioning
confidence: 99%
“…Alterations in S1R expression levels have been described in different models of HD, suggesting a potential link between S1R and disease pathology (8,18). Treatment with the S1R agonist, PRE084, has been shown to reverse S1R expression levels in PC6.3 neuronal cells and protect against mHTT-induced neurodegeneration (18).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study showed that another Sigma-1R agonist, PRE084, improved behavioral symptoms in a Parkinson's disease mouse model [191]. In another study, this same agonist promoted cell viability, reduced oxidative stress and decreased cleavage of caspases in mutant Htt-expressing cells [192], suggesting a possible therapeutic benefit of Sigma-1R agonists in HD.…”
Section: Therapeutic Targetingmentioning
confidence: 98%